Beyond adaptation: Pacific voices on health, identity, and rights amid climate loss and damage - Sharma, Sindra; Romanu, Varea; Varea, Rufino (Frontiers in Human Dynamics, 2025)
Loss and damage is an essential but under-examined aspect of climate justice, particularly for Pacific Small Island Developing States (PSIDS), disproportionately impacted despite minimal global emissions contributions. In the context of the International Court of Justice's ongoing advisory proceedings on states' climate obligations, this study explores the lived experience of health—related loss and damage in PSIDS as a contribution to the emerging international research agenda on climate-health justice. Using a qualitative thematic analysis (Braun and Clarke six-phase framework) of witness statements and documentary submissions from Vanuatu and the Melanesian Spearhead Group, supplemented by a targeted literature review, we identify interlocking themes of direct physical health impacts, psychosocial and cultural harm, erosion of traditional knowledge, strain on health systems and gender-specific vulnerabilities, this research identifies a complex tapestry of experienced harm tied inextricably to relational values of Pacific people. It is evident there are significant gender-differentiated health impacts including heightened exposure to infectious diseases, compromised nutrition, increased psychosocial trauma, loss of traditional medicinal knowledge, and deterioration of health infrastructure. Women face additional vulnerabilities linked to reproductive health, gender-based violence, and increased caregiving burdens exacerbated by climate-induced displacement and resource scarcity. The erosion of cultural identity, spiritual wellbeing, and connection to ancestral lands further compounds these issues. By synthesizing legal testimony and academic literature, the study contributes new evidence to international discussions on non-economic loss and damage and offers a framework for future comparative research across small-island contexts. Results underscore the urgent need for gender-responsive climate policies and culturally grounded interventions, integrating traditional knowledge systems and strengthening health infrastructures to address interconnected vulnerabilities effectively.